Inspice diligenter codices Philologische Studien zu Augustins Umgang mit Bibelhandschriften und -übersetzungen - Schirner, Rebekka S. (Millennium-Studien / Millennium Studies, 2015)
During the first centuries of the Christian era, a large number of discrepant Latin translations of the Old and the New Testaments were in circulation. Rebekka S. Schirmer examines St. Augustine`s comments about the problems raised by these texts, both descriptive and normative, and the extent to which Augustine`s engagement with different versions of the Bible employed philological methods of biblical exegesis.